Group Debates - Orr, Amy (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Debate TopicsDebate 1: School Choice: Should school districts implement school choice programs?Debate 2: Ability Grouping: Should children be divided into ability groups for instructions?Debate 3: Single-Sex Schools: Should single-sex public schools be allowed?Debate 4: Religion and Education: Should school-sponsored prayer (or the teaching of creation) be allowed in pubic schools?Debate 5: National Standards: Should the United States institute national education standards?